Choice of precipitant and calcination temperature of precursor for synthesis of NiCo2O4 for control of CO–CH4 emissions from CNG vehicles - Trivedi S.; Prasad R. (My University, 2025)
Compressed natural gas (CNG) is most appropriate an alternative of conventional fuel for automobiles. However, emissions of carbon-monoxide and methane from such vehicles adversely affect human health and environment. Consequently, to abate emissions from CNG vehicles, development of highly efficient and inexpensive catalysts is necessary. Thus, the present work attempts to scan the effects of precipitants (Na2CO3, KOH and urea) for nickel cobaltite (NiCo2O4) catalysts prepared by co-precipitation from nitrate solutions and calcined in a lean CO-air mixture at 400 °C. The catalysts were used for oxidation of a mixture of CO and CH4 (1:1). The catalysts were characterized by X-ray diffractometer, Brunauer–Emmett–Teller surface-area, X-ray photoelectron spectroscopy; temperature programmed reduction and Scanning electron microscopy coupled with Energy-Dispersive X-Ray Spectroscopy. The Na2CO3 was adjudged as the best precipitant for production of catalyst, which completely oxidized CO-CH4 mixture at the lowest temperature (T100 = 350 °C). Whereas, for catalyst prepared using urea, T100 = 362 °C. On the other hand the conversion of CO-CH4 mixture over the catalyst synthesized by KOH limited to 97% even beyond 400 °C. Further, the effect of higher calcination temperatures of 500 and 600 °C was examined for the best catalyst. The total oxidation of the mixture was attained at higher temperatures of 375 and 410 °C over catalysts calcined at 500 and 600 °C respectively. Thus, the best precipitant established was Na2CO3 and the optimum calcination temperature of 400 °C was found to synthesize the NiCo2O4 catalyst for the best performance in CO-CH4 oxidation. © 2017